Decolourization of azo, anthraquinone and triphenylmethane dyes using aerobic granules: Acclimatization and long-term stability. (January 2021) - Liu, Yong-Qiang; Maulidiany, Nopa; Zeng, Ping; Heo, Seongbong
Abstract: The long-term stability of aerobic granules is critical for decolourization of different dyes in textile wastewater. Here, we investigated dye decolourization and the stability of acetate-cultivated granules after exposure to dyes. Results show that granules can maintain excellent structure stability with the presence of azo and triphenylmethane dyes during a 200-day operation period, achieving biomass concentrations as high as 8–12 g L −1 and 90% and 100% decolourization efficiency, respectively. Aerobic granules, however, partially disintegrated after exposure to anthraquinone, resulting in dye decolourization efficiency ranging from 50 to 80% and a biomass concentration as low as around 0.5 g L −1 due to biomass wash-out. The study indicates that long-term granule stability is much dependent on the dye classes. The enrichment of specific species in granules for dye decolourization has not been affected by the granule structure. The specific dye decolourization rate and dye to microorganism ratio for anthraquinone were 5–6.5 and 13.5–16.4 times, respectively, higher than those for azo and triphenylmethane dyes, but the total reactor performance for anthraquinone decolourization is much poorer than azo and triphenylmethane dyes due to low biomass retention in the reactor. The results suggest the importance of stability of aerobic granules for biomass retention to achieve better treatment performance of dye-containing wastewater. For the first time, the long-term stability and decolourization performance of aerobic granules for treating anthraquinone and triphenylmethane dyes are reported here and compared with azo dye, which can be used to guide the treatment of real textile wastewater containing azo, anthraquinone and triphenylmethane dyes by aerobic granules. Highlights: Granules maintained long-term stability when decolourizing azo and triphenylmethane. Aerobic granules partially disintegrated after exposure to anthraquinone. Granules' structural stability is critical for biomass retention. Sludge treating anthraquinone had much higher specific dye decolourization rate. Sludge treating azo and triphenylmethane had much higher decolourization efficiency.